PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO MELALUI PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Saraswati, Ananda Dyah Ayu; ., Sadeli; Mulyanto, Indro Herry (Jurnal Ilmu Administrasi dan Bisnis, 2018)
This study aims to determine the effect of non-performing loan and loan to deposit ratio through profitability on the value of general banking companies listed on the Indonesia Stock Exchange. The population of this study is a public banking company listed on the Indonesia Stock Exchange (IDX) during the year 2013-2017. The sampling technique used is purposive sampling. Descriptive statistics, path analysis,and test of sobel used as data anlysis. The results showed non-performing loan (NPL) and loan to deposit ratio (LDR) had a significant effect on profitability. Non-performing loan (NPL), loan to deposit ratio (LDR) and profitability have a significant effect on the value of the company.The results of this test also shows the amount of indirect effect of non performing loan (NPL) through profitability to the value of the company is greater when compared with the amount of direct influence of non performing loan (NPL) to the value of the company. The results of this test also indicate the indirect effect of loan to deposit ratio (LDR) through profitability to the value of the company is greater when compared with the amount of direct influence of loan to deposit ratio (LDR) to the value of the company.Keyword: Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Profitability, Firm Value.